2021
DOI: 10.1016/j.celrep.2021.109775
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and function of motile ciliated cell types within ependymal lineages of the zebrafish brain

Abstract: Highlights d Glutamylated tubulin is enriched in cilia of foxj1-expressing cells in the zebrafish d Motile ciliated ependymal cells in the zebrafish forebrain are highly diverse d Gmnc drives the transition from mono-to multiciliated cells at juvenile stage d Lack of multiciliation does not impact brain and spine morphogenesis

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 117 publications
(225 reference statements)
5
67
0
Order By: Relevance
“…We used single cell transcriptome data from zebrafish telencephalon and the entorhinal cortex or superior frontal gyrus of human brains and human fetus datasets. Five datasets were downloaded from the Gene Expression Omnibus repository and used in the current study: human brain datasets GSE147528 [ 37 ] and microglia datasets [ 38 ], and the zebrafish datasets GSE118577 [ 41 ], GSE124162 [ 40 ], GSE161834 [ 42 ], and GSE186874. See Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…We used single cell transcriptome data from zebrafish telencephalon and the entorhinal cortex or superior frontal gyrus of human brains and human fetus datasets. Five datasets were downloaded from the Gene Expression Omnibus repository and used in the current study: human brain datasets GSE147528 [ 37 ] and microglia datasets [ 38 ], and the zebrafish datasets GSE118577 [ 41 ], GSE124162 [ 40 ], GSE161834 [ 42 ], and GSE186874. See Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The wt1a expression in ependymal cells could either reflect a specific developmental state or could indicate the existence of different ependymal subpopulations. This has also been suggested by the use of two enhancer trap lines that labelled distinct subsets of mCP epithelial cells in zebrafish ( Bill et al, 2008 ; Garcia-Lecea et al, 2008 ) and a very recent report using single cell RNA sequencing ( D'Gama et al, 2021 ).…”
Section: Discussionmentioning
confidence: 90%
“…The mechanism underlying development of communicating hydrocephalus in ciliopathy is still poorly understood. However, an increasing number of reports in mice, Xenopus and zebrafish have shown that the MCC (ependymal cells) lining the cerebral ventricles are important for: (i) CSF ‘near wall’ circulation [ 19 , 20 , 22 ], (ii) transport of nutrients and (iii) secretion of neuropeptides important for directional neural stem cell (NSC) migration (reviewed in Spassky and Meunier, 2017 [ 69 ]). Furthermore, genetic studies in humans with hydrocephalus and ciliopathy mouse models have uncovered defective neural stem cell proliferation including impaired cortical neurogenesis [ 60 62 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another contributor to CSF movement within the CNS involves the motile multi-ciliated cells (MCCs) lining the cerebral ventricles [ 18 , 19 ]. Ex situ studies using organotypic cerebral ventricle explant cultures from rodents and pigs [ 19 ], as well as in vivo experiments in Xenopus [ 20 , 21 ] and zebrafish [ 22 ], have revealed intricate dynamic patterns of CSF flow through the ventricles orchestrated by the MCCs. However, the role of MCCs in CSF transport and CNS fluid regulation is incompletely understood [ 23 ].…”
Section: Introductionmentioning
confidence: 99%